(untitled) (Bangladesh Journal of Zoology, 2019)
The study was to assess the infestation of red pumpkin beetle, epilachna beetle and fruit fly on 12 germplasm of sweet gourd Cucurbita moschata. The study also investigated the effect of weather parameters on the abundance of the insects. Red pumpkin beetle, epilachna beetle and fruit fly showed the highest level of infestation during 3rd week of December, 3rd week of January and 4th week of February, respectively. All the insects revealed the lowest level of infestation on BD274 and BD277 germplasm. Relative humidity had insignificant positive correlation with all the insects. Red pumpkin beetle showed significant positive correlation with temperature. Epilachna beetle exerted significant positive correlation with rainfall. The weather parameters jointly contributed 35.2% abundance of red pumpkin beetle and temperature individually depicted the highest effect (18.9%). Rainfall revealed the highest contribution (44.4%) on the abundance of epilachna beetle and the combined effect of the weather parameters was 66.5%. Temperature, relative humidity and rainfall showed 43.2% contribution on fruit fly abundance and the individual effect of relative humidity was the highest (27.0%). Bangladesh J. Zool. 47(2): 285-291, 2019